Bank stability, Covid-19, and Islamic bank financing in Indonesia - Agus Widarjono; Munrokhim Misanam (ITB AAS INDONESIA Surakarta, 2023)
The financial performance of Islamic banks is strongly influenced by the bank's ability to disburse their funds. The purpose of this study is to analyze the influence of Islamic bank fundamentals in influencing financing. Islamic bank fundamentals consist of stability, size, profitability, equity, efficiency, and financing risk. This study uses quarterly data to examine 13 Islamic commercial banks from 2014 to 2020. The method used is static panel data regression with unbalanced panel data of 334 observations. The results show that the Z-score, assets, ROA, and NPF have a positive effect on the financing of Islamic commercial banks. Meanwhile, the CAR and income cost ratio has a negative effect on the financing of Islamic commercial banks. Furthermore, the economic slowdown because of Covid-19 has reduced Islamic commercial bank financing. These findings indicate that profit, bank size, and stability are the main Islamic bank fundamentals that significantly influence the amount of Islamic bank financing.